PEMANFAATAN ALAT PERAGA IPA UNTUK PENINGKATAN PEMAHAMAN KONSEP FISIKA PADA SISWA SMA NEGERI I SAYURMATINGGI TAHUN PELAJARAN 2017/2018 - Elisa Elisa; Ainun Mardiyah (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2018)
Class action research (PTK) is carried out in order to know the increased understanding of the concept of physics on the subject of measurement through the utilization of the available IPA props in the school laboratory. Data obtained with the method of observation, and test method of the now method. Based on the results of observation understanding the physics of pre cycle amounted to 43.1% increased to 61.6% in cycle I and increased to 81.9% in cycle II. While the results of the now understanding the physics of the cycle I of 86.3% increase in cycle II becomes 90.9%. Meanwhile the results of tests on the pre-cycle average value of 63 with ketuntasan of 28.1% and has not yet reached the value of KKM who are already specified 71. In cycle I, the average value of the test results of students ' 71 with 34.4% and amounted to ketuntasan has reached the value of KKM. While on cycle II average value increased student test results that is being ketuntasan with 78 of 68.8%. Increased understanding of the concept of the learning results of physics students a minimum of 20% has been achieved. From those results showed that with the utilization of props IPA can improve understanding of physics students on the subject of measurement in SMA Negeri 1 Sayurmatinggi, so that utilization of props can be IPA be used as an alternative to increasing the understanding of physics. Keywords: class action research, understanding the concepts of physics